A medida do peso e o peso da medida: memória e acontecimento ressignificando o sentido sobre/do corpo - Rodrigues, Ana Paula Picagevicz (2023)
A body that is considered fat, or even appears to have a little fat, has long been frowned upon. In the historical evolution of the body, we can observe that it alternates between forms considered ideal to meet certain standards of health, beauty and social prestige. As a result, people try to shape their bodies to meet the social demands of the era, establishing and stagnating the meanings attached to slim and fat bodies. In this narrative, the fat body is classified as sick, among many other adjectives. Based on this research, and using French discourse analysis as a theoretical and methodological framework, this study aims to analyze whether the Body Mass Index (BMI) is a discursive event. To this end, our corpus of analysis consists of documents dealing with obesity: an official dossier of the World Health Organization (WHO) and other Brazilian institutions such as the Brazilian Association for the Study of Obesity and Metabolic Syndrome (ABESO). Based on Pêcheux's theory, we also examine how the medical discourse contained in these documents establishes and formulates the discourse of health and disease in relation to the body. We therefore consider it necessary to understand how this medical discourse functions. Through our analysis, we define BMI, a globally recognized diagnostic tool for obesity, as a discursive event because it redefines the meanings of health and disease for the body and categorizes them numerically. We consider that this occurs because medical discourse is institutionalized, as it constitutes the institutionalized practices in AIE health, which is why it has secured the place of being able to say about the body, health and illness. From this perspective, it is a discourse whose dominant mode of operation is authoritarian and which, because of the way it addresses the issue of obesity by focusing on weight loss as the only way to be healthy or to get healthy again, ends up reinforcing the inadequacy of the body and (re)producing a meaning effect in which being fat is being sick.